Helmholtz decomposition and semigroup theory to the fluid around a moving body - Bae, Hyeong Ohk (Bulletin of the Korean Mathematical Society, 2020)
To understand the interaction of a fluid and a rigid body, we use the concept of B-evolution. Then in a similar way to the usual Navier-Stokes system, we obtain a Helmholtz type decomposition. Using B-evolution theory and the decomposition, we work on the semigroup to analyze the linear part of the system.
Keywords: B-evolution; Fluid; Fractional power of operator; Helmholtz decomposition; Rigid body; Semigroup